2014
DOI: 10.1371/journal.pone.0108439
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma and Adipose-Derived Mesenchymal Stem Cells for Regenerative Medicine-Associated Treatments in Bottlenose Dolphins (Tursiops truncatus)

Abstract: Dolphins exhibit an extraordinary capacity to heal deep soft tissue injuries. Nevertheless, accelerated wound healing in wild or captive dolphins would minimize infection and other side effects associated with open wounds in marine animals. Here, we propose the use of a biological-based therapy for wound healing in dolphins by the application of platelet-rich plasma (PRP). Blood samples were collected from 9 different dolphins and a specific and simple protocol which concentrates platelets greater than two tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
(67 reference statements)
0
27
0
3
Order By: Relevance
“…This reduced clotting has been attributed to the contact of blood with water rather than air, as well as the need to sequester blood in stagnant reservoirs while diving [ 56 ]. Moreover, cetaceans show accelerated wound healing, reducing infection and accelerating tissue repair [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…This reduced clotting has been attributed to the contact of blood with water rather than air, as well as the need to sequester blood in stagnant reservoirs while diving [ 56 ]. Moreover, cetaceans show accelerated wound healing, reducing infection and accelerating tissue repair [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In humans, ASCs have been used to promote healing in radiation ischemia and perianal fistulas, and animal models show promise for the treatment of cardiovascular, genitourinary, and musculoskeletal disorders . In dolphins, ASCs have been isolated, cultured, and differentiated into multiple cell lineages, suggesting that they may have similar regenerative capabilities as in other mammalian species . Because the stem cells were derived from the sire of the patient, there was less risk of immune rejection of the cells than if they were derived from another, unrelated animal.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was collected from the periarterial venous rete at the distal ventral peduncle and processed to collect platelet‐rich plasma (PrP) using a veterinary benchtop kit primarily utilized in equine patients, which included spinning whole blood at 720 g for 15 min (Genesis CS‐2, Vet Stem Pharma, Poway, CA). Recent studies have shown that dolphin platelets have a significantly larger area compared with equine and human platelets, and an ideal centrifugation protocol for dolphin platelet concentration is 106 g (900 rpm) for 3 min, a much lower speed and shorter duration than was recommended with the benchtop kit . Because of the size difference between equine and cetacean platelets, this protocol was not successful in collecting PrP, and fresh plasma was used in all procedures.…”
Section: Case Reportmentioning
confidence: 99%
“…ADSCs cocultured with PRP secrete low chemokine concentrations and PRP also encourages downregulation of the strongly proinflammatory gene IL1B in ADSCs both of which suggest an anti‐inflammatory effect . ADSCs cultured with PRP from dolphins also show an enhanced ability to phagocytose suggesting a role in the inflammation stage of healing …”
Section: The Role Of Prp In Fat Graft Survivalmentioning
confidence: 99%
“…84 ADSCs cultured with PRP from dolphins also show an enhanced ability to phagocytose suggesting a role in the inflammation stage of healing. 85 Several in vitro studies have shown that PRP enhances proliferation of ADSCs 39,68,[86][87][88] and it can be used as a safe and reliable alternative to standard expansion media. 89,90 This enhanced proliferative effect on ADSCs does not affect their ability to differentiate 91 and a higher volume of ADSCs within a fat graft has been shown to have a positive effect on graft take and survival.…”
Section: The Role Of Prp In Fat Graft Survivalmentioning
confidence: 99%